Repeat percutaneous recanalizations of a discontinuous pulmonary artery: A very "lucky" vessel - Giovanbattista Calabri; Alberto Clemente; Giuseppe Santoro (Wolters Kluwer Medknow Publications, 2020)
Pulmonary artery (PA) discontinuity with ductal origin of a major pulmonary branch is a rare congenital anomaly that can be diagnosed as an isolated lesion or in association with major cardiac malformations. Arterial duct (AD) closure results in complete disappearance of the dependent PA, thus leading to the misdiagnosis of "congenital PA absence." Neonatal AD transcatheter recanalization is considered a cost-effective approach in view of later, lower-risk surgical recruitment of the disconnected PA. However, repeat percutaneous recanalizations of a completely occluded PA, the first one as native duct-dependent lesion and the second one several months after its surgical reimplantation, have so far never been reported in the literature. This paper reports on a neonate who serendipitously received at a few weeks of age the diagnosis of "congenital" absence of the right PA. She was successfully submitted to transcatheter AD recanalization and then surgical recruitment of the dependent PA about 8 months later. However, complete occlusion of the reconnected PA was diagnosed some few months after the surgical repair. This vessel was once again recruited by percutaneous approach and it is still patent and in catch-up growth after 6 months from the second recanalization procedure.